Cognitive Physics—The Enlightenment by Schrödinger, Turing, and Wiener and Beyond - Deyi Li (Intelligent Computing, 2023)
In the first half of the 20th century, 5 classic articles were written by 3 outstanding scholars, namely, Wiener (1894 to 1964), the father of cybernetics, Schrödinger (1887 to 1961), the father of quantum mechanics, and Turing (1912 to 1954), the father of artificial intelligence. The articles discuss the concepts such as computability, life, machine, control, and artificial intelligence, establishing a solid foundation for the intelligence of machines (how can machines recognize as humans do?) and its future development.